The Changing Status of Women in India: The Challenges Ahead Through Literature: Examining the Status of Women in India and the Continuing Struggles Through Literary Perspectives (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Women in the Indian society have been considered as inferior than men for many years. Because of such type of inferiority they have to face various issues and problems in their life. They have to go extra miles than men to prove themselves equivalent to men. People in the middle age were considering women as key to destruction so they never allowed women to go outside and participate in the social activities like men. Still in the modern age, women have to face many more problems in their daily life and struggle a lot to establish their career. Still there are many parents who prefer to have only boy baby and allow education to boys only. Women for them are only medium to keep family happy and healthy.“To call woman the weaker sex is a libel; it is man’s injustice to woman. If by strength is meant brute strength, then, indeed, woman is less brute than man. If by strength is meant moral power, then woman is immeasurably man’s superior: Has she not greater intuition, is she not more self-sacrificing, has she not greater powers of endurance, has she not greater courage? Without her man could not be. If non-violence is the law of our being, the future is with woman. Who can make a more effective appeal to the heart than woman?”